Adsorption of Anionic and Cationic Dyes on Chemically Modified Pomegranate Peel: A Isotherms and Kinetics Studies - Senthilkumar, T.; Rose Mir, Lima (Asian Journal of Chemistry, 2015)
The dyes used are highly toxic in nature also affecting the aquatic life and causing carcinogenic effects on human beings. Adsorption using activated carbon has received considerable interest from researchers globally due to its high efficiency in the treatment of effluents. In this present study pomegranate peel (Punica granatum sp.) was taken as an adsorbent. The methylene blue number, iodine number and surface area of pomegranate peel activated carbon were found to be 175 mg/g and 1360 mg/g and 686 m2/g, respectively. The anionic and cationic dye adsorption behaviour of pomegranate peel activated carbon (PPAC) was carried out using acid violet 12 (AV12) and basic brown 4 (BB4) onto pomegranate peel activated carbon. The isotherm studies were carried and it was found that the Langmuir isotherms fit well for the adsorption of both acid violet 12 and basic brown 4 on pomegranate peel activated carbon. Adsorption kinetics follows pseudo second order model and the adsorption process endothermic in nature.